Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00425-006-0252-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wheat crops with different chromosome ploidy: root-sourced signals, drought tolerance, and yield performance

Abstract: Pot-culture experiments were carried out to estimate the role of non-hydraulic root signals (nHRS) and the relation of these signals to drought tolerance and grain yield formation under drought stress in six wheat varieties. These were two modern hexaploid wheat (Triticum aestivum L., AABBDD) Plateau602 and Longchun8139-2, two diploid wheat (Triticum monococcum L., AB) MO1 and MO4, and two tetraploid wheat (Triticum dicoccum Schuebl L., AABB) DM22 and DM31. In the two diploid relatives, the nHRS was switched o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 26 publications
(40 reference statements)
4
79
1
1
Order By: Relevance
“…Compared to diploids, chromosome doubling (polyploidy) is often associated with increases in leaf thickness and area (Xu et al 2010) as well as in numbers of shoots and flowers (Xiong et al 2006, Li et al 2009). These anatomical and morphological variations generally lead to different physiological traits and ecological adaptations, e.g., higher drought tolerance (Li et al 1996, Xiong et al 2006, Li et al 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared to diploids, chromosome doubling (polyploidy) is often associated with increases in leaf thickness and area (Xu et al 2010) as well as in numbers of shoots and flowers (Xiong et al 2006, Li et al 2009). These anatomical and morphological variations generally lead to different physiological traits and ecological adaptations, e.g., higher drought tolerance (Li et al 1996, Xiong et al 2006, Li et al 2009).…”
Section: Introductionmentioning
confidence: 98%
“…These anatomical and morphological variations generally lead to different physiological traits and ecological adaptations, e.g., higher drought tolerance (Li et al 1996, Xiong et al 2006, Li et al 2009). Chromosome doubling can increase drought resistance in Lonicera japonica in relation to leaf anatomy improvement (Li et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the reduction of the lateral roots formation may be caused by the suppression of the activation of the lateral root's meristem, not because of the reduction of the initiation in the lateral root per se (9,10). Mutants with alterations in the development of lateral roots respond differently to drought stress (9,13). Suppression of the development of lateral roots by drought has been widely accepted as an adaptive response to ensure the plant's survival under unfavorable growing conditions (13).…”
Section: Abiotic Stress and Root Architecturementioning
confidence: 99%
“…Mutants with alterations in the development of lateral roots respond differently to drought stress (9,13). Suppression of the development of lateral roots by drought has been widely accepted as an adaptive response to ensure the plant's survival under unfavorable growing conditions (13). Nevertheless new lateral root formation and/or lateral root growth as well as the differentiation/elongation of root hairs lead to a considerable increase of the overall absorption surface (11).…”
Section: Abiotic Stress and Root Architecturementioning
confidence: 99%
See 1 more Smart Citation